Perceptions of Health Workers on Risk Factors of Medication Errors in Outpatient and Inpatient Services at X Hospital - Yoga Pribadi Utomo (Jurnal Admmirasi, 2021)
Health workers have a responsibility in preventing medication errors that occur from the prescription process to the administration of drugs. Medication errors are serious problems that have an impact on increasing the duration of hospitalization and treatment costs, patient mistrust which is usually followed by patient dissatisfaction with health care. The purpose of this study was to determine the risk factor analysis of medication errors in outpatient and inpatient care at the X Hospital.